1-2-3 zooborns! - Bleiman, Andrew; Eastland, Chris (Beach Lane Books, 2015)
"Attention, animal lovers! It's time to count along with a whole new crew of adorable zoo babies. Featuring irresistible animal photos, bouncy text, and a fact-filled glossary, this just might be the cutest counting book ever to hit the shelves!"--